The influence of college teachers' leadership style change and emotional regulation self-efficacy - Lu, Jing (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
The aim of this study is to examine the relationship between emotional regulation self-efficacy and leadership style change of university teachers by using the methods of questionnaire survey, literature research and establish a research model on the relationship between leadership style and emotional regulation self-efficacy. The questionnaire designed in this study mainly includes a number of questions about demography, including age, marriage, gender, major, education, efficient nature, position, teaching age, rank and so on. There are 10 questions about teachers' emotional regulation self-efficacy and 24 questions about transformational leadership style. There are 6 questions about transactional leadership style. The research and analysis of this study mainly adopts statistical methods such as variance analysis, reliability test, independent sample t test, descriptive statistical analysis, correlation analysis, hierarchical regression analysis and multiple regression analysis. The findings reveal that different leadership styles have different effects on teachers' emotional regulation self-efficacy in university system. Transformational leadership style has a negative correlation with teachers' emotional regulation self-efficacy, while transactional leadership style has a positive correlation with teachers' emotional regulation self-efficacy, which improves teachers' self-emotion management ability. In addition, transformational leadership style has a negative effect on the improvement of teachers' emotional regulation self-efficacy, but transactional leadership style has a positive effect on the improvement of college teachers' emotional regulation self-efficacy. A good leadership style can improve teachers' ability to self-control their emotions, promoting the efficient work of teachers, and has a positive effect on schools, students and teachers themselves. This study is of great value for a deeper understanding of teachers' emotional regulation self-efficacy.